An overview of molecular identification of insect fauna with special emphasis on chalcid wasps (Hymenoptera: Chalcidoidea) of India - Ajaz RASOOL; Tariq AHMAD; Bashir Ahmad GANAI; Shaziya GULL (Acta Agriculturae Slovenica, 2018)
Identifying organisms has grown in importance as we monitor the biological effects of global climate change and attempt to preserve species diversity in the face of accelerating habitat destruction. Classical taxonomy falls short in this race to catalogue biological diversity before it disappears. Differentiating subtle anatomical differences between closely related species requires the subjective judgment of highly trained specialists – and few are being trained in institutes today. DNA barcodes allow non-experts to objectively identify species – from small, damaged, or even industrially processed material. The aim of DNA barcoding is to establish a shared community resource of DNA sequences commonly used for identification, discrimination or taxonomic classification of organisms. It is a method that uses a short genetic marker in an organism's DNA to identify and distinguish its belonging from particular species, varieties or inter varieties. This simple technique has attracted attention from taxonomists, ecologists, conservation biologists, agriculturists, plant-quarantine officers and studies using the DNA barcode has rapidly increased. The extreme diversity of insects and their economical, epidemiological and agricultural importance have made them a major target of DNA barcoding. In this review, we present an overview of DNA barcoding of insects with emphasis on Chalcid wasps of India.